Improved safety performance through measurement, monitoring, and supervisory involvement - Allen, Richard R. (University of Wisconsin--Stout, 2018)
This paper summarizes the efforts of TC Electric to define a Safety Management System that is modern, aligned with organizational objectives and focused on attaining zero injury culture in the most effective and efficient means possible. TC Electric Safety Management System consists of six complementary and overlapping elements. The first and most essential element is Leadership and Employee Involvement. Remaining components of the system include; Training, Planning Performance Monitoring & Measurement, Incident Management, and Recordkeeping. It is the belief of the TC Electric leadership that through visibility and engagement combined with effective development and implementation of the Safety Management System we will achieve higher levels of performance and get steps closer to the zero-injury culture we are working towards. For TC Electric this systematic and collaborative approach represents significant change in mindset and culture across the company. For many years safety was viewed as a support function that while necessary did not directly create or add direct value to the organization. It is through recent declines in safety performance and realization that anything less than impeccable performance will affect TC Electric's ability to grow and flourish within the industry.
Keywords: Electric contracting; Industrial safety